Does central executive training and/or inhibitory control training improve emotion regulation for children with attention-deficit/hyperactivity disorder? A randomized controlled trial - Groves, Nicole B.; Chan, Elizabeth S. M.; Marsh, Carolyn L.; Gaye, Fatou; Jaisle, Emma M.; Kofler, Michael J. (Frontiers in Psychiatry, 2022)
Approximately 48-54% of children with attention-deficit/hyperactivity disorder (ADHD) have impairing difficulties with emotion regulation, and these difficulties are not ameliorated by first-line ADHD treatments. Working memory and inhibitory control represent promising intervention targets given their functional, if not causal, links with ADHD-related emotion dysregulation. This preregistered randomized controlled trial tested whether two digital therapeutic training protocols that have been previously shown to improve working memory (Central Executive Training/CET) and inhibitory control (Inhibitory Control Training/ICT) can improve emotion regulation in a sample of 94 children with ADHD aged 8-13 years (M = 10.22, SD = 1.43; 76% White/non-Hispanic; 29 girls). Results of Bayesian mixed model ANOVAs indicated both treatment groups demonstrated significant decreases in emotion dysregulation relative to pre-treatment at immediate post-treatment (parent report; d=1.25, BF10=8.04x1013, p<.001), at 1-2 months after completing treatment (teacher report; d=0.99, BF10 = 1.22x106, p < .001), and at 2-4-month follow-up (parent report; d=1.22, BF10=1.15x1014, p<.001). Contrary to our hypotheses, the CET and ICT groups demonstrated equivalent reductions in emotion dysregulation and maintenance of effects. Exploratory analyses revealed that results were robust to control for informant expectancies, ADHD medication status/changes, in-person vs. at-home treatment, child age, and time from treatment completion to post-treatment ratings. Thus, it appears possible that both working memory and inhibitory control are causally linked with ADHD-related emotion dysregulation. However, these hypotheses should be investigated with active control conditions that do not train executive functions prior to making decisions about the clinical utility of CET/ICT for the treatment of emotion dysregulation in ADHD.